Ezra Pound’s English translation practice of Li Bai’s Poems in Cathay based on Pierre Bourdieu’s sociological theory - Chang, Hongjing; Malini Ganapathy; Moindjie, Mohamed Abdou; Jiao, Chen (Penerbit Universiti Kebangsaan Malaysia, 2023)
To create a human community with a shared future, cultural exchanges between countries should be strengthened (Xi, 2020, p. 365). Classical Chinese poetry is an important part of the communication of Chinese culture. The most translated Li Bai’s poems in Cathay not only promoted better reception of Li Bai’s poems in a foreign context, but also injected powerful vitality into the Western literary world. This paper investigated Pound’s translation practice of Li Bai’s poems in Cathay and specifically interpreted Pound’s internal and external motivations in the selection of source text, textual features formed through translation strategies and the reception of English translation of Li Bai’s poems by drawing on three main concepts: “field”, “capital”, and “habitus” in Pierre Bourdieu’s sociological theory. It was found that Pound’s selection of Li Bai’s poems was made under the influence of utilitarian American sinology field and flashy literary field. Pound’s habitus with cosmopolitanism and historicism shaped by American sinology and literary fields initiated his translation idea of “translation as creation”, which further formed his translation strategies. Finally, Pound, with great social, cultural, and symbolic capitals, promoted better reception of Cathay, especially Li Bai’s poems. The findings of research revealed the powerful interpretation of Pierre Bourdieu’s sociological theory in translation and communication of literary works, which provided great recommendations for Chinese researchers and policymakers on how to better translate and communicate Chinese literature abroad for international literary exchanges.